2012
DOI: 10.1021/ja3074825
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of Lipidated Peptides in Fluid Bilayers: A Molecular-Level Investigation

Abstract: Nearest-neighbor recognition (NNR) measurements have been made for two lipidated forms of GlyCys, interacting with analogues of cholesterol and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) in the liquid-ordered (lo) and liquid-disordered (ld) phases. Interaction free energies that have been determined from these measurements have been used in Monte Carlo simulations to quantify the distribution of the peptides between liquid-ordered and liquid-disordered regions. These simulations have shown that signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…As discussed elsewhere, what distinguishes this technique from virtually all other methods that have been used to study nearest‐neighbor interactions is its directness and its extreme sensitivity; i.e., it can detect changes in free energies of interaction down to tens of calories per mole—a magnitude that is sufficient to significantly affect the lateral organization of membranes . In addition, NNR measurements can be used in combination with Monte Carlo simulations to quantify sub‐microscopic domains . This is in contrast to conventional fluorescence microscopy, which requires visualization and is not applicable to those membranes that do not exhibit l o − l d macroscopic phase separation; e.g., DPPC/POPC/cholesterol …”
Section: Figurementioning
confidence: 99%
“…As discussed elsewhere, what distinguishes this technique from virtually all other methods that have been used to study nearest‐neighbor interactions is its directness and its extreme sensitivity; i.e., it can detect changes in free energies of interaction down to tens of calories per mole—a magnitude that is sufficient to significantly affect the lateral organization of membranes . In addition, NNR measurements can be used in combination with Monte Carlo simulations to quantify sub‐microscopic domains . This is in contrast to conventional fluorescence microscopy, which requires visualization and is not applicable to those membranes that do not exhibit l o − l d macroscopic phase separation; e.g., DPPC/POPC/cholesterol …”
Section: Figurementioning
confidence: 99%
“…15 Thus, to a mixture of 3-(2-aminoethyldithio)propanoic acid hydrochloride salt (50 mg, 0.23 mmol) and triethylamine (100 μL) in anhydrous CHCl 3 (5 mL) was added N-(cholesteryl-carbonyloxy)-succinimide (194 mg, 0.38 mmol) in one portion. 18 The resulting solution was stirred overnight at room temperature, diluted with CHCl 3 (50 mL), and washed with water (50 mL, pH 3, HCl). The organic phase was then dried over MgSO 4 and concentrated under reduced pressure.…”
Section: Synthesis Of Exchangeable Homodimers Aa and Bbmentioning
confidence: 99%
“…17 Of particular significance is the fact that such measurements are highly sensitive and can detect differences in free energy down to tens of calories per mole. 18 By the use of this method, we have previously demonstrated that the condensing power of cholesterol is virtually identical to that of dihydrocholesterol, a commonly used surrogate (Chart 2). 19 The fact that a kinked isomer of dihydrocholesterol (i.e., coprostanol) has a substantially weaker condensing power has also provided strong support for a template effect by the steroid nucleus whereby the flexible acyl chains of a neighboring phospholipid are able to complement, perfectly, the steroid's planar nucleus to produce a large number of close hydrophobic contacts and tight packing.…”
Section: ■ Introductionmentioning
confidence: 96%
“…[23][24][25][26] As discussed elsewhere,w hat distinguishes this technique from virtually all other methods that have been used to study nearest-neighbor interactions is its directness and its extreme sensitivity;i .e., it can detect changes in free energies of interaction down to tens of calories per mole-a magnitude that is sufficient to significantly affect the lateral organization of membranes. [28] This is in contrast to conventional fluorescence microscopy,w hich requires visualization and is not applicable to those membranes that do not exhibit l o Àl d macroscopic phase separation;e .g.,DPPC/POPC/cholesterol. [28] This is in contrast to conventional fluorescence microscopy,w hich requires visualization and is not applicable to those membranes that do not exhibit l o Àl d macroscopic phase separation;e .g.,DPPC/POPC/cholesterol.…”
mentioning
confidence: 99%
“…[27] In addition, NNR measurements can be used in combination with Monte Carlo simulations to quantify sub-microscopic domains. [28] This is in contrast to conventional fluorescence microscopy,w hich requires visualization and is not applicable to those membranes that do not exhibit l o Àl d macroscopic phase separation;e .g.,DPPC/POPC/cholesterol. [29][30][31] In brief,t he NNR method measures the mixing behavior of membrane components by analyzing equilibrium distributions of corresponding disulfide-based dimers.T ypically, ah eterodimer that is composed of two lipids of interest, AB,i sp artially reduced to monomers in ah ost membrane ( Figure 1).…”
mentioning
confidence: 99%